Housing Assistance Payment: Potential impacts on financial incentives to work - Barra Roantree; Tim Callan; Michael Savage; John Walsh (The Economic and Social Research Institute (ESRI), 2019)
Since March 2017, a new income-related housing support for those with a long-term housing need called Housing Assistance Payment (HAP) has been available throughout the state. This paper examines the potential impact on financial work incentives of transferring long-run Rent Supplement recipients onto HAP with tenants' rental contributions assessed through a national Differential Rents scheme, initially proposed by the Housing Agency but yet to be implemented. While such a system would strengthen the financial incentive for most long-term Rent Supplement claimants to be in full-time paid work, a small minority would continue to face quite weak incentives. This is driven by the receipt of multiple means-tested benefits - in particular, jobseekers allowance and one-parent family payment - which results in some low-income individuals facing very high effective marginal tax rates from relatively low levels of earnings.
Keywords: Q12; Q52; D90; 330; regulatory compliance; farmer behaviour; nitrates; Ireland